Massive tarsal coalition with extended tarsometatarsal coalition in a child: a case report - Yang, Lei; Yang, Xiaodong; Jiang, Jun; Tang, Xueyang (Frontiers in Pediatrics, 2024)
Tarsal coalition refers to the union of two or more tarsal bones, which mostly involves the calcaneonavicular and talocalcaneal joints; it is rarely found in multiple unions or unions extended to the metatarsal bones. Nearly 50% of cases occur bilaterally and can be either symmetrical or asymmetrical. We described a rare case of symmetrically bilateral tarsal coalitions involving all the tarsal bones, except for the medial cuneiform, and extending to the fourth metatarsal bones in a 5-year-old boy. This patient exhibited no obvious symptoms and had not received any further intervention, only regular follow-up. To our knowledge, this is the first report of this type of massive coalition involving the union of six tarsals and one tarsometatarsal bilaterally.